The Type III Secretion System (T3SS)-Translocon of Atypical Enteropathogenic Escherichia coli (aEPEC) Can Mediate Adherence - Santos, Fernanda F.; Yamamoto, Denise; Abe, Cecilia M.; Bryant, Jack A.; Hernandes, Rodrigo T.; Kitamura, Felipe C.; Castro, Felipe S.; Valiatti, Tiago B.; Piazza, Roxane M. F.; Elias, Waldir P.; Henderson, Ian R.; Gomes, Tânia A. T. (Frontiers in Microbiology, 2019)
The intimin protein is the major adhesin involved in the intimate adherence of atypical enteropathogenic Escherichia coli (aEPEC) strains to epithelial cells, but little is known about the structures involved in their early colonization process. A previous study demonstrated that the type III secretion system (T3SS) plays an additional role in the adherence of an Escherichia albertii strain. Therefore, we assumed that the T3SS could be related to the adherence efficiency of aEPEC during the first stages of contact with epithelial cells. To test this hypothesis, we examined the adherence of seven aEPEC strains and their eae (intimin) isogenic mutants in the standard HeLa adherence assay and observed that all wild-type strains were adherent while five isogenic eae mutants were not. The two eae mutant strains that remained adherent were then used to generate the eae/escN double mutants (encoding intimin and the T3SS ATPase, respectively) and after the adherence assay, we observed that one strain lost its adherence capacity. This suggested a role for the T3SS in the initial adherence steps of this strain. In addition, we demonstrated that this strain expressed the T3SS at significantly higher levels when compared to the other wild-type strains and that it produced longer translocon-filaments. Our findings reveal that the T3SS-translocon can play an additional role as an adhesin at the beginning of the colonization process of aEPEC.